HERMENEUTIC PERSPECTIVES ON CONTEMPORARY TRANSLATION METHODOLOGY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Hermeneutics – traditionally the philosophy of understanding texts – has become a central lens for theorising and practising translation. By reframing the translator as both reader and second order author, hermeneutic approaches foreground situated interpretation, subjectivity and the historical embeddedness of meaning. This article synthesises foundational insights from Schleiermacher and Gadamer with recent empirical studies on translator cognition, computer assisted environments and performance oriented “event” views of translation. It shows how the hermeneutic paradigm reshapes four domains: (1) literary translation as the fusion of horizons, (2) specialised translation where pre understanding interacts with terminological regimes, (3) emerging multimodal and staged translations, and (4) translator education. By mapping convergences and controversies, the discussion clarifies hermeneutics’ unique contribution to a plural disciplinary landscape and outlines research priorities for an age of artificial intelligence.